A scoping review of food and nutrition literacy programs. - Cabezas, María-Francisca; Nazar, Gabriela (Health Promotion International, 2023)
The impact of food literacy (FL) and nutrition literacy (NL) programs on lifestyles and health is recognized in the literature, yet few studies systematize it. This study aims to deepen the understanding of FL/NL from the characterization of programs in terms of (i) theoretical foundations, conceptualization and measuring instruments; (ii) characterization of the FL/NL programs and results and (iii) limitations and future directions declared. A scoping review of original articles addressing FL/NL programs from the Web of Science, Scopus and PubMed databases published between 2015 and 2023. There was a somewhat restricted view of the construct and the absence of a clear boundary between FL and NL. Half of the studies reported theoretical foundations. The most used model was Social Cognitive Learning Theory. More significant development of programs was observed in Australia, using quasi-experimental designs. Most of the studies informed positive results. Limitations of the studies related to the sampling process, absence of a control group and lack of follow-up. It is suggested that long-term interventions consider economic, social and cultural factors. Despite that theoretical and empirical aspects should be revised, FL/NL programs are a suitable strategy to mitigate the social and health effects of inadequate nutrition.